British Sculpture in the Twentieth Century - Nairne, Sandy; Serota, Nicholas (London : Whitechapel Art Gallery, 1981)
Abrahams, Ivor ; Agar, Eileen ; Annesley, David ; Armitage, Kenneth ; Atkinson, Lawrence ; Auerbach, Arnold ; Ayrton, Michael ; Barker, Clive ; Bayes, Gilbert ; Bedford, Richard ; Belsky, Franta ; Brock, Thomas ; Brown, Ralph ; Burt, Lawrence ; Butler, Reg ; Caro, Anthony ; Chadwick, Lynn ; etc.
British Sculpture in the Twentieth Century, The Whitechapel Art Gallery, London, shown in two parts: Part One: Image and Form 1901-50, 11 September - 1 November, 1981 ; Part Two: Symbol and Imagination 1951-80, 27 November - 24 January, 1982
boek
Keywords: Groot-Brittannië